Analysis of Organizational Culture towards Organizational Change – Myth or Science?: Is the Organizational Culture of the Management Student Association (HMM) of Muhammadiyah Bandung University Forever? - Aghnia Yasyfa; Anisa Roshy Rosdian; Hesti Hisani Latifah Hamdah; Sofa Parihah Nurasiah (Indo Publishing, 2026)
ABSTRACT Organizational culture is often assumed to be fixed and resistant to change (the